2020
DOI: 10.1016/j.ultrasmedbio.2020.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Transcranial Sonography for Evaluating Substantia Nigra Hyper-echogenicity in Patients with Parkinson's Disease

Abstract: To determine the diagnostic performance of transcranial sonography (TCS) in assessing increased echogenic area of the substantia nigra (SN) in patients with Parkinson's disease (PD). Institutional review board approval was obtained for this retrospective study. A total of 278 PD patients (mean age: 64.7 § 9.8 y, 100 women) and 300 healthy control patients (mean age: 63.6 § 9.3 y, 97 women) were referred for TCS assessment of SN hyper-echogenicity (SN+) from June 2016 to December 2018. Two sonographers independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
4
4
0
Order By: Relevance
“…The poorer performance in visual-spatial perception and motor skills and the higher depression scores seen in women compared to men was similar to the general population [ 20 , 21 , 22 ]. The higher hyperechogenicity found in men compared to women has previously been reported by three different groups in China [ 23 , 24 , 25 ]. Whether it is correlated with the higher rate of PD found in males or an actual difference between genders should be further studied.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The poorer performance in visual-spatial perception and motor skills and the higher depression scores seen in women compared to men was similar to the general population [ 20 , 21 , 22 ]. The higher hyperechogenicity found in men compared to women has previously been reported by three different groups in China [ 23 , 24 , 25 ]. Whether it is correlated with the higher rate of PD found in males or an actual difference between genders should be further studied.…”
Section: Discussionsupporting
confidence: 61%
“…Among the tests without age adjustment, we noticed a weak correlation between age with motor skills, MoCA, and smell. Although TCS was shown to be positively correlated to age in healthy controls [ 25 ], it seems that this correlation does not exist with PD patients [ 26 ]. This suggests that the TCS score may be a stable marker in patients with PD throughout the course of the disease [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The larger echogenic areas observed in the patients with parkinsonism are consistent with the broader literature describing ultrasonography in PD 27 . Based on a reference cutoff of 20 mm 2 from prior literature, 26 TCS measurements from participants without parkinsonism—including one individual who subsequently developed parkinsonism—were largely in the normal range, whereas most of those with parkinsonism showed abnormally elevated values.…”
Section: Discussionsupporting
confidence: 82%
“…The larger echogenic areas observed in the patients with parkinsonism are consistent with the broader literature describing ultrasonography in PD. 27 Based on a reference cutoff of 20 mm 2 from prior literature, 26 TCS measurements from participants without parkinsonism-including one individual who subsequently developed parkinsonism-were largely in the normal range, whereas most of those with parkinsonism showed abnormally elevated values. The current data do not rule out a subtle statistical increase in overall mean nigral echogenicity in individuals with GBA1 mutation carriers without parkinsonism relative to healthy genetic controls, as observed in one recent report that did not include post-sonography clinical follow-up 28 ; however, they do suggest a paucity of clinically significant TCS-measured pathology in this group.…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff obtained was similar to other studies published with traditional machines from var-ious manufacturers and in different countries, given that the majority of the studies worldwide show that an optimal cutoff is between 0.20 and 0.25 cm 2 Vivó-Orti et al (2013). in their research used traditional equipment and found the area of 0.22 cm 2 as a cutoff point in the 90th percentile, and the ROC curve was constructed with 75 subjects with PD and 91 healthy individuals Xu et al (2020),. in their research, made two ROC curves, one for each traditional equipment used to discriminate subjects with PD (n = 278) from healthy individuals (n = 300) to measure SN hyperechogenicity.…”
supporting
confidence: 80%